2010
DOI: 10.1111/j.1399-3089.2010.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Pig islet xenotransplantation acceptance in a Latin-American diabetic population

Abstract: Progress in porcine islet xenotransplantation has been accompanied by studies on acceptance of this new procedure by patients, health professionals or the general public. Such studies have not been done in the Latin-American population. We conducted a questionnaire in 108 diabetes patients (insulin-dependent, n = 53; insulin-independent, n = 55) in a public hospital in Argentina. The questions addressed the general perception of the xenotransplant procedure and specific items related to the outcome (achieving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Seventy-five percent indicated they would accept the porcine tissue even if it only reduced their insulin requirements, temporarily prevented the progression of secondary complications, or needed to be repeated every six months. Interestingly, 40% indicated that they believe living with porcine cells could cause them psychological distress (Abalovich et al, 2010). This is in contrast to a French study from 5 years previous, where it was found that the proportion of individuals with type 1 diabetes willing to accept a transplant was much lower.…”
Section: Cultural Views Of Porcine Islet Xenotransplantationcontrasting
confidence: 54%
“…Seventy-five percent indicated they would accept the porcine tissue even if it only reduced their insulin requirements, temporarily prevented the progression of secondary complications, or needed to be repeated every six months. Interestingly, 40% indicated that they believe living with porcine cells could cause them psychological distress (Abalovich et al, 2010). This is in contrast to a French study from 5 years previous, where it was found that the proportion of individuals with type 1 diabetes willing to accept a transplant was much lower.…”
Section: Cultural Views Of Porcine Islet Xenotransplantationcontrasting
confidence: 54%
“…Therefore, the findings of the comparative analysis of the attitude of the personal in the Hospital Eva Perón workers that were not in- In numerous studies, the acceptance of xenotransplantation in different human communities has been studied in recent years. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] This acceptance depends on knowledge on efficacy and safety and is-as mentioned by Carl Groth-related to fear of the unknown, what he called "fear factor." 30 However, it is difficult to establish the weight of this factor as a barrier to apply this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In numerous studies, the acceptance of xenotransplantation in different human communities has been studied in recent years . This acceptance depends on knowledge on efficacy and safety and is—as mentioned by Carl Groth—related to fear of the unknown, what he called “fear factor.” However, it is difficult to establish the weight of this factor as a barrier to apply this treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some have raised concerns regarding zoonotic infections, it appears that the risk of infectious transmission is lower than that observed in human islets . Porcine islet transplantation would appear to be cost effective compared to standard management, is generally morally acceptable to most diabetic patients, and regulatory issues appear soluble . There are, however, formidable immunologic barriers which must be circumvented to permit successful engraftment in humans.…”
Section: Current Surgical Needs—the Tip Of a Large Icebergmentioning
confidence: 99%